2016
DOI: 10.5296/jad.v2i2.10042
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style and Perceived Organisational Politics as Predictors of Organisational Commitment among Civil Servants in Osun State

Abstract: This study examined the predictive roles of leadership styles and perceived organisational politics on organisational commitment among Civil Servant in Osun State. Primary data for the study were collected from a total of 248 Civil Servants in Osun state using the stratified random sampling technique. Three standardized Psychological Scales were used in the study. These were the Supervisors Behaviour Descriptive Questionnaire (SBDQ), Perception of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…This meant that the perception held by employees in the indigenous Ghanaian bank about the politics in their organisations did not moderate the impact that their managers/supervisor’s leadership style had on their engagement to work. These findings are in contrast with those found in similar studies by Fashola et al (2016), Harris and Kacmar (2005); Hall et al (2006); Hu and Bentler (1999), who all found that there is some significant impact of POPS on leadership styles and employees work engagement. A plausible reason is perhaps the highly regulated system within which banks operates.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…This meant that the perception held by employees in the indigenous Ghanaian bank about the politics in their organisations did not moderate the impact that their managers/supervisor’s leadership style had on their engagement to work. These findings are in contrast with those found in similar studies by Fashola et al (2016), Harris and Kacmar (2005); Hall et al (2006); Hu and Bentler (1999), who all found that there is some significant impact of POPS on leadership styles and employees work engagement. A plausible reason is perhaps the highly regulated system within which banks operates.…”
Section: Discussioncontrasting
confidence: 88%
“…Although many organisational factors tend to influence behaviours at work, politics at the workplace is experienced by all and is fundamental in everyday workplace activities such as decision-making, resource allocation and communication (Fashola et al , 2016). Employees vary in their perception of organisational politics depending on their level of involvement in political processes in an organisation (Chhetri et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the studies conducted by Fashola, Akanni & Ajila, (2016); Kimura, (2012) and Kim, Eisenberger & Baik, (2016) support the findings of the given study with respect to the relationship of organizational politics with leadership styles and employee's commitment. The studies found that organizational politics is positively related to the transformational and democratic styles of leadership while showing a negative correlation with autocratic and transactional styles of leadership.…”
Section: Discussionsupporting
confidence: 82%
“…Organizational politics and leadership style are closely related variables because the leadership of an organization plays an important role in shaping the overall culture and structure of an organization in terms of employee's behaviors, attitudes, and overall workplace environment (Fashola, Akanni & Ajila, 2016). It is further commented that the leadermember relationship is one of the important determinants of organizational politics in an organization that determines the possible implications of organizational politics on the underlying outcomes of an organization.…”
Section: Organizational Politicsmentioning
confidence: 99%